Pengaruh Kualitas Pelayanan Customer Service Rumah Sakit Karya Bhakti Pratiwi terhadap Kepuasan Pasien - Afrah, Fahira (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
There is a gap between the services received and patient expectations of the quality of service of Karya Bhakti Pratiwi Hospital, such as uncomfortable waiting room facilities, customer service officers who provide inaccurate information, customer service that does not respond quickly to patient requests / complaints, customer service unfriendliness, and customer service attitudes that do not show attention and empathy for the needs and conditions of patients. So the researcher has the aim of knowing the extent of the influence of customer service quality on patient satisfaction, especially at Karya Bhakti Pratiwi Hospital (RSKBP). Researchers use social exchange theory and the concept of service quality using the SERVQUAL model which consists of tangible, reliability, responsiveness, assurance, and empathy. This research uses a quantitative approach through an explanatory method conducted on 100 RSKBP patients by determining the sample with simple random sampling. The results of this study indicate that the five dimensions of RSKBP customer service quality have a significant influence on patient satisfaction. The direction of the influence is positive, meaning that the better the quality of service provided by RSKBP customer service, the better patient satisfaction will be.